APOL1 High-Risk Genotype is Not Associated With New or Worsening of Proteinuria or Kidney Function Decline Following COVID-19 Vaccination - Sarah E. Nystrom; Karen L. Soldano; Micki Rockett; Somenath Datta; Guojie Li; Daniel Silas; Melanie E. Garrett; Allison E. Ashley-Koch; Opeyemi A. Olabisi (Kidney International Reports)
Introduction: SARS-CoV-2 infection increases systemic inflammatory cytokines which act as a second-hit driver of Apolipoprotein L1 (APOL1)-mediated collapsing glomerulopathy. SARS-CoV-2 vaccination also increases cytokines. Recent reports of new glomerular disease in individuals with APOL1 high-risk genotype (HRG) following SARS-CoV-2 vaccination raised the concern SARS-CoV-2 vaccination may also act as a second-hit driver of APOL1-mediated glomerulopathy. Methods: We screened 1507 adults in the Duke’s Measurement to Understand Reclassification of Disease of Cabarrus and Kannapolis (MURDOCK) registry and enrolled 105 eligible participants with available SARS-CoV-2 vaccination data, prevaccination and postvaccination serum creatinine, and urine protein measurements. Paired data were stratified by number of APOL1 risk alleles (RAs) and compared within groups using Wilcoxon signed rank test and across groups by analysis of variance. Results: Among 105 participants, 30 (28.6%) had 2, 39 (37.1%) had 1, and 36 (34.3%) had 0 APOL1 RA. Most of the participants (94%) received at least 2 doses of vaccine. Most (98%) received the BNT162B2 (Pfizer) or mRNA-1273 (Moderna) vaccine. On average, the prevaccine and postvaccine laboratory samples were drawn 648 days apart. There were no detectable differences between pre- and post-serum creatinine or pre- and post-urine albumin creatinine ratio irrespective of the participants’ APOL1 genotype. Finally, most participants with APOL1 RA had the most common haplotype (E150, I228, and K255) and lacked the recently described protective N264K haplotype. Conclusion: In this observational study, APOL1 HRG is not associated with new or worsening of proteinuria or decline in kidney function following SARS-CoV-2 vaccination. Validation of this result in larger cohorts would further support the renal safety of SARS-CoV-2 vaccine in individuals with APOL1 HRG.